The effect of electromagnetic field on decreasing and increasing of the growth and proliferation rate of dermal fibroblast cell. Issue 4 (13th July 2020) - Naghibzadeh, Mehran; Gholampour, Seifollah; Naghibzadeh, Majid; Sadeghian‐Nodoushan, Fatemeh; Nikukar, Habib
Abstract: Maintaining the health of dermal fibroblast cells and controlling their growth and proliferation would directly affect the health of skin tissues. The present study encompassed three control and three experimental specimens, which were different in terms of the duration of exposure to electromagnetic field (EMF) and intensity. With a decrease in intensity from 2 to 1 mT during 24, 48, and 72 h after exposing the cells to EMF, the frequency of the sample fibroblast cells increased by 60.3%, 144.9%, and 90.1%, respectively. With an increase in intensity from 3 to 4 mT during 48 and 72 h of exposure to EMF, the frequencies of the sample fibroblast cells decreased by 6.8% and 86.7%, respectively. It seems to be possible to achieve the most desirable condition to help the restoration of wounds and skin lesions through decreasing the exposure intensity from 2 to 0.5 mT and increasing EMF exposure time from 24 to 72 h simultaneously and non‐invasively. The most desirable approach to improve the treatment of skin cancers non‐invasively is to increase the intensity from 3 to 5 mT and to enhance EMF exposure time from 48 to 72 h.